2023
DOI: 10.1002/aoc.6982
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale metallic‐organic frameworks as an advanced tool for medical applications: Challenges and recent progress

Abstract: Recently, metal-organic frameworks (MOFs) have received a lot of interest for application in many fields ranging from catalysis, energy storage, and gas sensing to chemosensory and biomedicine owed to their flexible composition, tunable porosity, and easy functionalization ability. In particular, nanoscale MOFs have been broadly investigated as carriers for the delivery of therapeutics to cancerous organs owed to their high encapsulating capacity and controlled cargo release, versatility, biodegradability, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 217 publications
0
6
0
Order By: Relevance
“…For future research, breakthroughs need to be continuously made to promote the widespread application of MOFs in the medical field. [174] MOFs have been widely applied in biomedical applications, specifically in drug loading and drug delivery systems, particularly for antiviral and anticancer compounds. However, solubility and long-term stability in aqueous, alkaline, and acidic media and toxicity of the selected metal salts and organic linkers for the preparation of MOFs as well as the issues associated with biocompatibility and biodegradability are major concerns for the applications of drug delivery.…”
Section: Nanomedical Applications In Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…For future research, breakthroughs need to be continuously made to promote the widespread application of MOFs in the medical field. [174] MOFs have been widely applied in biomedical applications, specifically in drug loading and drug delivery systems, particularly for antiviral and anticancer compounds. However, solubility and long-term stability in aqueous, alkaline, and acidic media and toxicity of the selected metal salts and organic linkers for the preparation of MOFs as well as the issues associated with biocompatibility and biodegradability are major concerns for the applications of drug delivery.…”
Section: Nanomedical Applications In Mofsmentioning
confidence: 99%
“…For future research, breakthroughs need to be continuously made to promote the widespread application of MOFs in the medical field. [ 174 ]…”
Section: Progress In the Mof Applicationsmentioning
confidence: 99%
“…For example, Tela et al combined MIL-53 and Ag Nps to evaluate the antifungal activity of the material against Aspergillus flavus. The experimental results showed that the growth inhibition was up to 64% [ 118 ]. Furthermore, Fe-MOFs can be used to combat parasites, such as Leishmania parasites and Toxoplasma gondii.…”
Section: Bio-related Applications Of Fe-mofsmentioning
confidence: 99%
“…Metal-organic framework (MOF) nanomaterials, such as MOF-PNIPAM membranes [ 8 ], ZIF-8 MOF [ 9 ], PCL/MOF-545 [ 10 ], HKUST-1 [ 11 ], and ZIF-8 [ 12 ], are widely used for drug delivery, diagnosis [ 13 , 14 ], as adsorbents [ 15 ], and for photocatalysis, for the removal of sulfonamide, CIP, and tetracycline antibiotics, respectively, from an aqueous solution through the adsorption technique. In addition, MOFs have attracted significant attention in photocatalysis technology, due to their semiconductor-like behavior, which transfers photogenerated charges to the reactive sites of a ligand-to-metal charge transfer (LMCT) for the in-situ decomposition of organic compounds, to form CO 2 and water [ 16 ].…”
Section: Introductionmentioning
confidence: 99%